Dynamics of Coupled Structures, Volume 4 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Allen, Matt; Mayes, Randall L.; Rixen, Daniel (Conference Proceedings of the Society for Experimental Mechanics Series,, 2016)
Dynamics of Coupled Structures, Volume 4. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the fourth volume of ten from the Conference brings together contributions to this important area of research and engineering. Th e collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Experimental Dynamic Substructuring • Structural Coupling of Nonlinear Structures • Analytical/Numerical Modeling of Joints • Industrial Applications of Substructuring • Source Identifi cation & Transfer Path Analysis • Human Induced Vibrations • Damping & Friction.